Integrative analysis of COL6A3 in lupus nephritis: insights from single-cell transcriptomics and proteomics - Mou, Lisha; Zhang, Fan; Liu, Xingjiao; Lu, Ying; Yue, Mengli; Lai, Yupeng; Pu, Zuhui; Huang, Xiaoyan; Wang, Meiying (Frontiers in Immunology, 2024)
Lupus nephritis (LN), a severe complication of systemic lupus erythematosus (SLE), presents significant challenges in patient management and treatment outcomes. The identification of novel LN-related biomarkers and therapeutic targets is critical to enhancing treatment outcomes and prognosis for patients. In this study, we analyzed single-cell expression data from LN (n=21) and healthy controls (n=3). A total of 143 differentially expressed genes were identified between the LN and control groups. Then, proteomics analysis of LN patients (n=9) and control (SLE patients without LN, n=11) revealed 55 differentially expressed genes among patients with LN and control group. By comparison of single-cell and proteomics data, we discovered that COL6A3 is significantly upregulated, highlighting it as a critical biomarker of LN. Our findings emphasize the substantial involvement of COL6A3 in the pathogenesis of LN, particularly noting its expression in mesangial cells. Through comprehensive proteinprotein interaction network and functional enrichment analyses, we uncovered the pivotal role of COL6A3 in key signaling pathways including integrin-mediated signaling pathways, collagen-activated signaling pathways, and ECM-receptor interaction, suggesting potential therapeutic targets. The diagnostic utility is confirmed by its correlation with disease progression and renal function metrics of the glomerular filtration rate. Receiver operating characteristic analysis further validates the diagnostic value of COL6A3, with the area under the receiver operating characteristic curve values of 0.879 in the in-house cohort, and 0.802 and 0.915 in tubular and glomerular external cohort samples, respectively. Furthermore, immunohistochemistry and qPCR experiments were consistent with those obtained from the scRNA-seq and proteomics studies. These results proved that COL6A3 is a promising biomarker and therapeutic target, advancing personalized medicine strategies for LN.